The impact of carbon pricing on energy costs and energy security in Türkiye - Atılgan, Süleyman; Alım, Muzaffer; Çöteli, Resul (Türkiye Enerji Stratejileri ve Politikaları Araştırma Merkezi (TESPAM), 2026)
The increase in the greenhouse effect leads to the acceleration of global warming, the disruption of ecosystem balance and climate changes. Climate changes due to global warming lead to results such as melting glaciers, rising sea levels and increasing frequency of extreme weather events. The increase in greenhouse gas emissions has been continuously growing and become a significant threat in the fight against climate change. One of the most effective ways to prevent this increase is carbon pricing. In this study, firstly, data regarding to CO2 emissions are presented, then carbon pricing policies and applications such as carbon tax and emission trading system are discussed. The relationship between energy and CO2 emissions is examined by applying the Pearson correlation analysis method on the data. Then, the change in the unit costs of energy resources according to different carbon price scenarios is calculated by the Levelized Unit Cost of Energy (LCOE) method through Net Present Value (NPV) analysis. Higher carbon pricing further enhances the cost competitiveness of renewables which makes them a more economically favorable option for future energy investments. For developing countries, implementing carbon pricing policies incentivizes domestic renewable energy investment, reducing dependence on energy imports and thereby strengthening energy security and economic resilience.
Keywords: Energy; Enerji; Renewable Energy Resources; Yenilenebilir Enerji Sistemleri